Pengaruh konformitas sosial terhadap perubahan identitas mahasiswa di lingkungan perguruan tinggi - Anas sh, Moh Azwar (Maliki Interdisciplinary Journal, 2026)
A change in self identity among students is something that often happens in the university environment, especially when they are in transition from adolescence to adulthood. One one think that affects the change is social conformity, whis is a person’s tendency to adapt to the rules, values, and group actions in order to be accepted in their social environment. This research wants to see how social conformity affects the identity changes of students in the university environment. The method used in this study is a qualitative approach with descriptive analysis, which describes social phenomena based on the reality that occurs in the field. The results of the discussion show that social pressure from the campus environment, such as the desire to be accepted in society, can encourage students to adjust their identity, both in terms of appearance, behavior, and values ​​​​adopted. In addition, lack of self-confidence and the search for identity also contribute to the strengthening of social conformity among students. On the other hand, identity change does not always have a negative impact, because in some cases it can help individuals adjust to the new environment. However, if done excessively, this can lead to the loss of original and authentic identity. Therefore, it is important to have self-awareness and a supportive campus environment so that students can develop without losing their personal identity.